"Trust neither the Horse, nor Modernity": Explicating Mahmoud Darwish's Allusions to Babylon, Sodom and Ancient Indians in "Counterpoint: Edward Said". Issue 2 (2nd July 2020) - Qabaha, Ahmad
ABSTRACT: This paper examines the allusions to Babylon, Sodom and the Red Indians in Mahmoud Darwish's tribute to Edward Said, which he entitled "Counterpoint." This paper argues that these allusions add a new understanding to the significant contribution of Darwish's poetry to postcolonial literature. It shows these allusions suggest that the postcolonial narrative is an encompassing narrative that is continuously renewed and retold by meta-narratives by authors whose peoples experienced colonialism for two reasons: first, colonialism has never ended, but it continues with new shapes; and second, allusions in postcolonial literature aim at reciprocating "postcolonial solidarity." This paper further demonstrates that these allusions gesture toward sharing the belief that indigenous stories and struggles are more powerful and rooted when waged together against the colonialist negation of the history and culture of native people.